A social cognition perspective on autonomous technology. (September 2021) - Frischknecht, Ruth
Abstract: The last several years have been characterized by an increasing autonomization of technology. Advanced technologies are now capable of learning and interacting. These capabilities expand the scope in which technology can be used. As a result, these increasingly autonomous machines and programs are completing an ever-growing number of tasks in collaboration with humans. This is why it is important to determine whether increasing levels of autonomy affect how technical systems are perceived by their human counterparts. An online survey experiment using vignettes to describe technical systems with varying levels of autonomy was employed to test the effects of technical autonomy on the dimensions of social cognition (i.e., warmth and competence) and mind perception (i.e., experience and agency). The findings show that increasing levels of technical autonomy impacted how the technical systems were socially perceived. More specifically, the findings suggest that the more autonomous a technical system is, the more competence and agency it will be ascribed. Conversely, increasing levels of technical autonomy had no effect on the ascription of warmth and experience. These results highlight that technical autonomy is relevant to and effectively shapes social judgements regarding technology. Highlights: This study investigates the effect of technical autonomy on social cognition and mind perception dimensions. The effect of technical autonomy is systematically explored in a survey experiment using theoretically grounded vignettes. Technical autonomy is a relevant variable as social perceptions change under increasing levels of technical autonomy. The more autonomous a technical system is the more competence and agency it is ascribed.